Pytochemical profile of Aloe ferox Mill. across different regions within South Africa - Sipho Goge; Karishma Singh; Lisa V. Komoreng; Roger M. Coopoosamy (AOSIS, 2023)
Background: Aloe ferox is an indigenous medicinal plant that is widely used for its various medicinal and pharmacological properties. Despite the medicinal importance and various applications of the species, it is surprising that little is known about the extent of geographical differences in its major chemical compounds. Also, the correlation between different geographic regions and variations in plant phytochemicals has received less attention. Aim: This study sought to investigate the presence of biologically active compounds in the leaf extracts of A. ferox from different geographical regions across South Africa. Setting: This study was set in different regions within South Africa. Methods: Phytochemical screening was performed qualitatively using established standard procedures involving chemical reagents such as hexane, chloroform and methanol and a series of reactions to determine the presence of phytocompounds of biological importance. Results: The study revealed that A. ferox leaves possess several classes of phytocompounds such as alkaloids, tannins, terpenoids, glycosides, phenolics, flavonoids, saponins and fixed oils and fats across various samples. Mucilage was absent across the samples. Conclusion: The study revealed eight classes of phytochemical compounds present on A. ferox leaves in three different geographic regions, which is consistent with the previous studies; however, further research is needed to enhance the study through qualitative research, gas chromatography-mass spectrometry and high-performance liquid chromatography analyses to validate phytochemical variations and their therapeutic effects. Contribution: This study contributes to the existing knowledge of the therapeutic Aloe genus.